2013
DOI: 10.1108/jmp-07-2013-0223
|View full text |Cite
|
Sign up to set email alerts
|

Hiring retirees: impact of age norms and stereotypes

Abstract: Purpose -Our study investigates the role of managers in the re-employment of early retirees and focuses on the effect of managers' age norms and stereotypes on managers' employment decisions.Design/methodology/approach-A combination of a factorial study and a survey was conducted. First, information on the age norms and stereotypes was collected. Secondly, profiles of hypothetical retired job applicants were presented to the employers, who were asked to make a specific hiring decision. The information collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 47 publications
2
38
0
2
Order By: Relevance
“…It furthermore shows the importance of top managers in directing organizations' practices, and thereby the importance of leadership in the emergence and effects of norms (e.g., Ostrom, 2000). Next to directing line managers' selection behavior regarding older job applicants (Karpinska et al, 2013a;Oude Mulders et al, 2014), agerelated workplace norms also influence organizations' practices on a higher level. This may imply that age-related workplace norms of top managers 'trickle down' through the organization, affecting other people's norms in the process, and thereby affecting organizations' behavior.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It furthermore shows the importance of top managers in directing organizations' practices, and thereby the importance of leadership in the emergence and effects of norms (e.g., Ostrom, 2000). Next to directing line managers' selection behavior regarding older job applicants (Karpinska et al, 2013a;Oude Mulders et al, 2014), agerelated workplace norms also influence organizations' practices on a higher level. This may imply that age-related workplace norms of top managers 'trickle down' through the organization, affecting other people's norms in the process, and thereby affecting organizations' behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Awareness campaigns could create more awareness about age discrimination, age equality, and qualities of older workers. In particular, more attention to culturally expected retirement timing and age equality is warranted, since age-related workplace norms are more directly related to employment behavior by organizations and managers than stereotypes of older workers (see also Karpinska et al, 2013a). Especially when it comes to stimulating employment outside the societal norm of 'normal retirement age', policy makers should try to change top managers' norms about career duration and retirement timing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As indicated by Van Solinge and Henkens (2007), retirement age norms illustrate the appropriate time to retire, and they affect retirement decisions of older workers. Previous research by Karpinska et al (2013a;2013b) has shown that age norms held by managers do affect their hiring and retention decisions regarding older workers, and form a barrier to prolonged employment.…”
Section: Managers' Characteristicsmentioning
confidence: 99%
“…We chose to use the cutoff of 50 years to distinguish older workers from younger workers. Even if there is little consensus on the chronological age (or ages) at which an "older worker" is defined, a number of previous studies have used 50 years old as cut-off (McCarthy et al, 2014) and, furthermore, according to managers' opinion, the "limit of employment" seems to be 50 years (see, Karpinska et al, 2013). Based on previous findings, which showed that the same age stereotypes are shared by people of different ages, we expect that:…”
Section: Age Stereotypes In the Workplacementioning
confidence: 99%